Sosialisasi Stop Bullying Di SDN Kuin Cerucuk 1 Banjarmasin - Sa’adah Erliani; Muhammad Arifin; Ria Mayasari; Arina Wulandari (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2025)
Bullying is a serious problem that has a negative impact on children's psychological and social development, especially in elementary school environments. This community service activity aims to increase awareness of students and teachers at SDN Kuin Cerucuk 1 Banjarmasin about the dangers of bullying and the importance of creating a safe, comfortable, and empathetic school environment. The method of implementing the activity is in the form of socialization and counseling through visual media, interactive discussions, role simulations, and distribution of educational leaflets. This activity involves all students from grades I to VI and teachers. The results of this activity show an increase in students' understanding of the forms of bullying and their impacts. In addition, teachers also showed enthusiasm in supporting ongoing bullying prevention programs. Based on the evaluation results, 87% of participants stated that they better understood how to identify and prevent bullying. In conclusion, this socialization succeeded in building collective awareness between students and teachers to jointly reject all forms of bullying. It is hoped that this activity will be the first step in forming an inclusive, tolerant, and child-friendly school culture.